2011
DOI: 10.1177/1741826711400545
|View full text |Cite
|
Sign up to set email alerts
|

Persistent lipid abnormalities in statin-treated patients and predictors of LDL-cholesterol goal achievement in clinical practice in Europe and Canada

Abstract: Nearly half of statin-treated patients missed their therapeutic LDL-cholesterol goal, highlighting a gap between recommendations and clinical practice. Better achievement of LDL-cholesterol therapeutic goal was found among patients at high cardiovascular risk, those on high statin doses or using combination therapy, and patients managed by specialists. Results suggest that residual dyslipidemia in statin-treated patients at low cardiovascular risk may be reduced by increasing statin dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
88
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 30 publications
16
88
0
4
Order By: Relevance
“…Many studies showed that there is a strong disparity between guidelines and clinical reality with regard to statin use and LDL-C goal attainment. (6,(21)(22)(23)(24) A summary of published data on lipid goal attainment is provided in table 3. It must be acknowledged, however, that poor lipid goal attainment to a great deal is due to physician inertia rather than poor patient adherence; physician inertia is therefore not the major focus of this work.…”
Section: Where Do We Stand: Poor Adherence To Statin Usementioning
confidence: 99%
“…Many studies showed that there is a strong disparity between guidelines and clinical reality with regard to statin use and LDL-C goal attainment. (6,(21)(22)(23)(24) A summary of published data on lipid goal attainment is provided in table 3. It must be acknowledged, however, that poor lipid goal attainment to a great deal is due to physician inertia rather than poor patient adherence; physician inertia is therefore not the major focus of this work.…”
Section: Where Do We Stand: Poor Adherence To Statin Usementioning
confidence: 99%
“…Overall, 48.2% of patients did not achieve their LDL-C goal (according to European Society of Cardiology [ESC] recommendations) [37]. Among high-risk patients (defined as established CVD, diabetes, or ESC-SCORE C5%), 46.8% did not attain an LDL-C level \97 mg/dl [38]. The more recent DYSIS-II study, which enrolled 3867 patients with recent ACS and 6794 patients with stable coronary heart disease (CHD), showed that, among those receiving lipid-lowering treatment, only 26% of patients with ACS and 31% of those with stable CAD achieved an LDL-C \70 mg/dl.…”
Section: Inability Of Some Patients To Attain Desirable Low-mentioning
confidence: 99%
“…Control of elevations in LDL-C is reported at about 48% in the EU [Gitt et al 2012], 53% in the UK [Kotseva et al 2012], but was decidedly improved at approximately 73% for all patients in the Lipid Treatment Assessment Project 2 (L-TAP-2) [Waters et al 2009]. In high-risk patients, however, target attainment was lower at 67%, and only 35% of patients with two or more risk factors achieved optional goals of LDL-C < 1.8 mmol/L.…”
Section: Emerging Drug Therapiesmentioning
confidence: 99%